Left Atrial Appendage Occlusion Device and Novel Oral Anticoagulants Versus Warfarin for Stroke Prevention in Nonvalvular Atrial Fibrillation: Systematic Review and Meta-Analysis of Randomized Controlled Trials. (October 2015) - Briceno, David F.; Villablanca, Pedro; Cyrille, Nicole; Massera, Daniele; Bader, Eric; Manheimer, Eric; Aagaard, Philip; Ferrick, Kevin; Gross, Jay; Kim, Soo Gyum; Krumerman, Andrew; Palma, Eugen; et al.
Abstract : Background—: Nonvalvular atrial fibrillation is the most common arrhythmia. Patients with nonvalvular atrial fibrillation are at increased risk of stroke; therefore, we evaluated the efficacy and safety of different approaches to prevent this major complication. Methods and Results—: We conducted electronic database searches of phase III randomized controlled trials. The groups were novel oral anticoagulants, Watchman left atrial appendage occlusion device (DEVICE), and warfarin. Efficacy outcomes were stroke or systemic embolism, and all-cause mortality. Safety outcome was major bleeding and procedure-related complications. A subgroup analysis of the elderly population was done. We used random-effects model to compare pooled outcomes and tested for heterogeneity. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed for each outcome. Seven randomized controlled trials (n=73 978) were included. There was a significant difference favoring novel oral anticoagulants for systemic embolism (OR, 0.84; 95% CI, 0.72–0.97; P =0.01), all-cause mortality (OR, 0.89; 95% CI, 0.84–0.94; P <0.001), and safety outcomes (OR, 0.79; 95% CI, 0.65–0.97; P =0.026) compared with warfarin. No difference was seen between DEVICE and warfarin for efficacy end points; however, DEVICE had more complications (OR, 1.85; 95% CI, 1.14–3.01; P =0.012). In the elderly (6 randomized controlled trials, n=30 699), systemic embolism was favored with novel oral anticoagulants over warfarin (OR, 0.77; 95% CI, 0.68–0.87; P ⩽0.001). No evidence of significant publication bias was found. Conclusions—: Novel oral anticoagulants is superior to warfarin for stroke prevention in nonvalvular atrial fibrillation. This benefit was also observed in the elderly population. DEVICE is a reasonable noninferior alternative to warfarin for stroke prevention, but cautious use is essential given safety concerns. Abstract : Supplemental Digital Content is available in the text.